Environmental Reporting: Significance and Issues: A Case from Sri Lanka - Rajapakse, B. (My University, 2012)
Recent surveys on environmental reporting of developed countries suggest that stakeholders’ demand for environmental information and the reporting of firm impact on the physical environment have dramatically increased during the last few years whereas environmental reporting of developing countries lag behind that of developed countries. However, it is concluded that existing environmental reporting even in developed countries are deficient and not of a standard to satisfy the information requirements of various groups of stakeholders. This is mainly due to an inadequate supply of environmental information as there are impediments to encourage environmental reporting at firm as well as at national level.